Circadian clock does not play an essential role in daylength measurement for growth-phase transition in Marchantia polymorpha - Kanesaka, Yuki; Inoue, Keisuke; Tomita, Yuki; Yamaoka, Shohei; Araki, Takashi (Frontiers in Plant Science, 2023)
Daylength is perceived as a seasonal cue to induce growth-phase transition at a proper time of a year. The core of the mechanism of daylength measurement in angiosperms lies in the circadian clockcontrolled expression of regulators of growth-phase transition. However, the roles of the circadian clock in daylength measurement in basal land plants remain largely unknown. In this study, we investigated the contribution of circadian clock to daylength measurement in a basal land plant, the liverwort Marchantia polymorpha. In M. polymorpha, transition from vegetative to reproductive phase under long-day conditions results in differentiation of sexual branches called gametangiophores which harbor gametangia. First, we showed that a widely used wild-type accession Takaragaike-1 is an obligate long-day plant with a critical daylength of about 10 hours and requires multiple long days. Then, we compared the timing of gametangiophore formation between wild type and circadian clock mutants in long-day and short-day conditions. Mutations in two clock genes, MpTIMING OF CAB EXPRESSION 1 and MpPSEUDO-RESPONSE REGULATOR, had no significant effects on the timing of gametangiophore formation. In addition, when M. polymorpha plants were treated with a chemical which lengthens circadian period, there was no significant effect on the timing of gametangiophore formation, either. We next observed the timing of gametangiophore formation under various non-24-h light/dark cycles to examine the effect of phase alteration in circadian rhythms. The results suggest that daylength measurement in M. polymorpha is based on the relative amount of light and darkness within a cycle rather than the intrinsic rhythms generated by circadian clock. Our findings suggest that M. polymorpha has a daylength measurement system which is different from that of angiosperms centered on the circadian clock function.